Serial determinations of oxygen profiles in infants with respiratory distress. - Holman, W L (1978)
Serial oxygen profiles were determined for 20 newborn infants by measuring arterial tensions at low (20--40%), intermediate (60--80%), and high (95--100%) levels of inspired oxygen. These points were plotted on a graph which estimated the percentage of venous admixture at any particular level of inspired oxygen. The infants' oxygen profiles were then determined. As much as 25% of venous admixture could be attributed to the presence of diffusion and distribution abnormalities in infants with hyaline membrane disease. A substantial number of infants showed increased shunting at high levels of oxygen, even in the presence of continuous distending airway pressure. It is hypothesised that a rising shunt is due to complete absorption of gas in poorly ventilated alveoli at high concentrations of inspired oxygen, resulting in the presence of atelectasis and redistribution of blood to poorly ventilated areas.